Pennsylvania Academic Career/Technical Training Alliance Initiative: Engaging Youth in School and Work - Goodman, Marna (2015)
This research offers a feasibility study on the effectiveness of the Pennsylvania Academic Career Technical Training Alliance (PACTT) at engaging youth in school and work upon return to the community. The sample included adjudicated youth from Allegheny County, Pennsylvania committed to PACTT-affiliated residential facilities and who discharged between July1, 2011 and June 31, 2012. An overview of the PACTT Initiative, with specific attention to its core elements, is presented and examined in the context of Ecological Systems Theory. Secondary data was analyzed using logistic regression to measure the overall impact of the five PACTT elements, dosage of PACTT elements, and the influence of a youth's personal characteristics on engagement in school and/or work upon discharge. Although the results revealed statistically non-significant relationships among four of the PACTT elements and the outcome variables, statistically significant positive relationships were identified between the following sets of variables: (a) obtaining a HSD/GED during placement (one of the PACTT elements) and (b) age at discharge(one of the personal characteristics) and engagement in work post-discharge. Additionally, a statistical trend showing a positive relationship between length of stay and school engagement was identified. Taken together, this feasibility study shows a limited relationship between the PACTT program and the youth outcomes the program is designed to impact. However, the study does offer a first step towards a more robust evaluation of PACTT and provides an evaluative framework for future researchers interested in examining the effectiveness of PACTT